Management of a Hospıtal Wastes Located in Izmir - Delia Teresa Sponza; Duygu Ardeniz Ören (The Global Environmental Engineers, 2019)
In this study, the solid wastes produced from a hospital and the present waste management procedures were investigated. The management of solid wastes of the hospital were discussed and some novel waste management techniques were determined to treat the solid wastes. The solid wastes should be collected in special coloured bags, they should be labelled and should be stored in special storage area, and should be disposed by the licensed companies according to Waste Management Regulation. The application of the waste separation at the source throughout the hospital decreases the waste disposal fees. The management of hazardous wastes coming from the hospital should be handled as proposed by the Waste Management Regulations.